Court decisions on post-divorce children’s livelihood: Islamic law analysis on their practices in Indonesia and Malaysia - Fauzul Hanif Noor Athief; Resti Hedi Juwanti (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
A divorce is indeed never expected to happen in a marriage. However once it happens, the important thing which must be taken into account is the consequence of the divorce where the issue pertinent to children’s livelihood is one of it. This study tried to probe into how Malaysia and Indonesia whose most of the population was Muslims adopted the Fiqh concept in terms of post-divorce children’s livelihood in their regulations. Since there always be difference between theory and practice, the real implementation of the decisions will also be examined on the basis of legal norms. This study directly explores the laws and Court decisions for further assessment based on several indicators. It is found that the legislation and the Court decisions of the two countries had adopted the concept of Fiqh yet with a couple of particular notes. It is also found that there is a chance of providing livelihood for illegitimate children in the law and practice of both countries.